Are Boys Ready for Human Papillomavirus Vaccine? A National Study of Boys in Malaysia - Wong, Li Ping; Alias, Haridah; Yusoff, R.N.A.R.M.; Sam, I-Ching; Zimet, Gregory D. (Lippincott, Williams & Wilkins, 2019)
Background The aim of this study was to investigate factors associated with the willingness of boys to accept the human papillomavirus (HPV) vaccine. Methods A nationwide cross-sectional survey among Secondary One male students in Malaysia. Results Among 2823 respondents, knowledge about HPV infection and the HPV vaccine was extremely poor. The mean total knowledge score was only 3.17 (SD ± 2.14), out of a possible score of 10. The majority of respondents were unaware that vaccinating boys can help protect girls against HPV infection (81.6%), and HPV is a sexually transmitted infection (70.1%). Many had the misconception that only females get HPV (78.9%). In multivariable analysis, the factors associated with the intention to receive the HPV vaccination were: agreeing boys need to be vaccinated against HPV infection (odds ratio [OR], 2.05; 95% confidence interval [CI], 1.57-2.68), perceiving their parents might allow them to get the HPV vaccine (OR, 1.66; 95% CI, 1.18-2.34), perceived susceptibility to HPV infection (OR, 1.63; 95% CI, 1.06-2.52), and attending a rural school (OR, 1.49; 95% CI, 1.14-1.95). Conclusions Public health educational programs that are focused and tailored on parents consenting to HPV vaccination for boys at a young age can be useful in improving HPV vaccination rates among boys. There is also a pressing need to educate boys about the benefits of HPV vaccination in males and about HPV disease susceptibility to facilitate adoption of the HPV vaccine by young adults in the future. © 2019 American Sexually Transmitted Diseases Association. All rights reserved.